Tingkat Pemahaman Pajak, Penerapan E-Filing Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Selama Masa Pandemi Dengan Peran Lingkungan Sebagai Variabel Moderasi - Purba, Jamian; Wulandari, Dian Sulistyorini; Widyaningsih, Winda (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
ABSTRACT This study examines the effect of tax comprehension level, e-filing implementation, and tax penalties on individual taxpayer compliance with the role of the environment as a moderating variable. The population used in this study comprises taxpayers who understand the process of reporting and paying taxes. The data consists of 100 respondents collected through a questionnaire using partial least squares (PLS) data analysis. Based on statistical tests, the results show that the tax comprehension level does not have a significant effect on individual taxpayer compliance. The implementation of e-filing has a significant effect on individual taxpayer compliance. Tax penalties do not have an effect on individual taxpayer compliance. The role of the environment has a significant effect on individual taxpayer compliance. The tax comprehension level on individual taxpayer compliance, when moderated by the role of the environment, does not have a significant effect. The implementation of e-Filing on individual taxpayer compliance, when moderated by the role of the environment, has a significant effect. Tax penalties on individual taxpayer compliance, when moderated by the role of the environment, have a significant effect.